Factors associated with the risk of obstructive sleep apnea among open-angle glaucoma patients attending ophthalmology clinic in a Teaching Hospital, Malaysia - Muteb, Obed Twesan (2021)
Glaucoma is the most prevalent cause of permanent vision loss in the world. There have been some findings that have shown an association between open-angle glaucoma (OAG) and obstructive sleep apnea (OSA) in Caucasian and Chinese people, however, there have been no any similar studies published from South-East Asia. Detection of OSA in a glaucoma patient and initiating optimal treatment for both conditions will arrest the progress of both medical problems. Therefor this study objective was to determine the factors (socio-demography, medical co-morbidities) associated with the risk of OSA in OAG patients, as well as the relationship between glaucoma parameters and OSA by using the STOP-BANG questionnaire. This study was a cross-sectional study that was carried out in the Ophthalmology clinic in Hospital Pengajar Universiti Putra Malaysia, Serdang, Seri Kembangan from November 2019 to January 2021using a convenience sampling method to collect 442 respondents, with a response rate of 98.2% (males:245 ,55.4%, females:197,44,6%). Ethical approval was obtained from both National Medical Research Register (NMRR) and institutional Ethics Committee for Research Involving Human Subject (JKEUPM). Participants who fulfilled the inclusion criteria (aged ≥40 years with underlying open-angle glaucoma) were recruited. Research tools used were a validated questionnaire that had questions on socio-demography, ocular history, medical history, and also incorporated the STOP-BANG questionnaire. STOP-BANG questionnaire was used to classify patients as low risk ≤ 2) and moderate to high risk (score ≥ 3) of OSA. The patients also underwent a full ocular and complete ear, nose and throat examination. SPSS v25.0 was used to perform the statistical analysis. Level of significance was taken as ≤ 25.0. The mean age was 64.2 ± 8.9 years. The prevalence of moderate to high risk of OSA was 247(55.9%) that includes females (n=51,11.54%), and male (n=196,44.34%). Predictors of moderate to high risk of OSA by using the multiple logistic regression analysis were males (odds ratio (OR) = 189.7, 95% confidence interval (CI) = 55.21, 651.69), individuals with a higher BMI (OR = 1.23, 95% CI =1.14, 1.33), participants who were diabetics (OR = 3.1, 95% CI = 1.45, 6.63) and having hypertension (OR = 70.73, 95% CI = 22.59,221.50). This study reported that in glaucoma patients, the prevalence of moderate to high risk of OSA is higher than that of the general population. The treating ophthalmologist should consider screening for OSA in glaucoma patients, especially in those with factors identified as predisposing to OSA.